Failing backward? EU citizenship, the Court of Justice, and Brexit. Issue 10 (3rd October 2021) - Conant, Lisa
ABSTRACT: Developments in European Union (EU) citizenship rights meet expectations of the 'failing forward' framework that fuses insights from liberal intergovernmentalist and neofunctionalist integration theories, whereby member state disagreements produce an incomplete form of EU citizenship that fails to treat individuals equally. Legal challenges to discriminatory treatment fit neofunctionalist expectations, with the European Court of Justice (ECJ) extending social rights for EU citizens incrementally. Resulting tensions between the evolution of rights and intergovernmental contestation fuels 'failing forward' in the form of the de-coupling of law and practice. Despite their limited impact, expanding rights sparked politicization that suggests postfunctionalist failures of European solidarity and declining trust in the ECJ. Most damaging to integration, however, is the lack of voting rights in national elections for mobile EU citizens, which (1) enabled the British exit (Brexit) crisis, an outcome of 'failing backward' and (2) persists as a serious EU democratic deficit.